A new species of Aulacospermum (Umbelliferae) from Uzbekistan - Pimenov, Michael G.; Tojibaev, Komiljon Sh.; Degtjareva, Galina V.; Ostroumova, Tatiana A.; Zakharova, Ekaterina A.; Karimov, Farkhod I.; Samigullin, Tahir H. (Phytotaxa, 2023)
A new species, Aulacospermum multicaule from the southwestern Tian-Shan (eastern part of the Kurama Range in Uzbekistan), is described and illustrated. The new species is related to A. roseum and differs in the features of stem (9–11 vs. solitary or 2–4), stem base (mostly black membranous vs. brown fibrous remains of petioles and sheaths of leaves of the preceding year at rootstock), and petals (yellowish vs. white). Molecular analysis of nrITS sequence data provides further evidence to recognize A. multicaule as a member of the genus Aulacospermum.